At Westonci.ca, we make it easy to get the answers you need from a community of informed and experienced contributors. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
Sure, let's eliminate the parameter [tex]\( t \)[/tex] from the given parametric equations and express [tex]\( y \)[/tex] as a function of [tex]\( x \)[/tex].
### Step 1: Express [tex]\( t \)[/tex] in terms of [tex]\( x \)[/tex] from the first equation
The first equation is:
[tex]\[ x = 2 - 3t \][/tex]
We can solve for [tex]\( t \)[/tex]:
[tex]\[ x = 2 - 3t \][/tex]
[tex]\[ 3t = 2 - x \][/tex]
[tex]\[ t = \frac{2 - x}{3} \][/tex]
### Step 2: Substitute [tex]\( t \)[/tex] into the second equation
The second equation is:
[tex]\[ y = 5 + t \][/tex]
Substitute the expression we found for [tex]\( t \)[/tex]:
[tex]\[ y = 5 + \frac{2 - x}{3} \][/tex]
### Step 3: Simplify the expression
To make this simpler, let's separate the fraction:
[tex]\[ y = 5 + \frac{2}{3} - \frac{x}{3} \][/tex]
[tex]\[ y = 5 + \frac{2}{3} - \frac{x}{3} \][/tex]
[tex]\[ y = 5\frac{3}{3} + \frac{2}{3} - \frac{x}{3} \][/tex]
[tex]\[ y = \frac{15}{3} + \frac{2}{3} - \frac{x}{3} \][/tex]
[tex]\[ y = \frac{15 + 2 - x}{3} \][/tex]
[tex]\[ y = \frac{17 - x}{3} \][/tex]
### Step 4: Express [tex]\( y \)[/tex] in the form of [tex]\( y = mx + b \)[/tex]
[tex]\[ y = -\frac{x}{3} + \frac{17}{3} \][/tex]
Therefore, the slope [tex]\( m \)[/tex] is [tex]\(-\frac{1}{3}\)[/tex] and the [tex]\( y \)[/tex]-intercept [tex]\( b \)[/tex] is [tex]\(\frac{17}{3}\)[/tex].
So, the expression for [tex]\( y \)[/tex] in terms of [tex]\( x \)[/tex] is:
[tex]\[ y = -\frac{1}{3} x + \frac{17}{3} \][/tex]
Thus, placing the constants into the required form, [tex]\( y = -\frac{\boxed{1}}{\boxed{3}} x + \boxed{17/3} \)[/tex].
### Step 1: Express [tex]\( t \)[/tex] in terms of [tex]\( x \)[/tex] from the first equation
The first equation is:
[tex]\[ x = 2 - 3t \][/tex]
We can solve for [tex]\( t \)[/tex]:
[tex]\[ x = 2 - 3t \][/tex]
[tex]\[ 3t = 2 - x \][/tex]
[tex]\[ t = \frac{2 - x}{3} \][/tex]
### Step 2: Substitute [tex]\( t \)[/tex] into the second equation
The second equation is:
[tex]\[ y = 5 + t \][/tex]
Substitute the expression we found for [tex]\( t \)[/tex]:
[tex]\[ y = 5 + \frac{2 - x}{3} \][/tex]
### Step 3: Simplify the expression
To make this simpler, let's separate the fraction:
[tex]\[ y = 5 + \frac{2}{3} - \frac{x}{3} \][/tex]
[tex]\[ y = 5 + \frac{2}{3} - \frac{x}{3} \][/tex]
[tex]\[ y = 5\frac{3}{3} + \frac{2}{3} - \frac{x}{3} \][/tex]
[tex]\[ y = \frac{15}{3} + \frac{2}{3} - \frac{x}{3} \][/tex]
[tex]\[ y = \frac{15 + 2 - x}{3} \][/tex]
[tex]\[ y = \frac{17 - x}{3} \][/tex]
### Step 4: Express [tex]\( y \)[/tex] in the form of [tex]\( y = mx + b \)[/tex]
[tex]\[ y = -\frac{x}{3} + \frac{17}{3} \][/tex]
Therefore, the slope [tex]\( m \)[/tex] is [tex]\(-\frac{1}{3}\)[/tex] and the [tex]\( y \)[/tex]-intercept [tex]\( b \)[/tex] is [tex]\(\frac{17}{3}\)[/tex].
So, the expression for [tex]\( y \)[/tex] in terms of [tex]\( x \)[/tex] is:
[tex]\[ y = -\frac{1}{3} x + \frac{17}{3} \][/tex]
Thus, placing the constants into the required form, [tex]\( y = -\frac{\boxed{1}}{\boxed{3}} x + \boxed{17/3} \)[/tex].
Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.